Atlas of Cyathodium Kunze Species from India - Vayalil, Sarath Ramesan Velu; Syamala, Sunukumar Soma; Sarayu, Manoj Gopal (Asian Journal of Biological and Life Sciences)
It has been shown that India is one of the mega-biodiversity nations in the world. Incredible floral variety may be attributed to India’s many biogeographic regions, each of which has its distinct geographical zones and physico-climatic characteristics. Miniature amphibians most closely represent the three bryophyte lineages: mosses, hornworts, and liverworts. Mosses are classified as their category and make up the most diverse and extensive group. The purpose of the present research is to compile a list of all of India’s known Cyathodium species utilizing data gathered from herbaria owned by a variety of organizations as well as any publications that are pertinent to the topic. Eight different species of Cyathodium were discovered by a group of Indian bryologists. A great number of species share characteristics and looks that might be confusing. It is necessary to revise Cyathodium in order to get rid of the overlapping and convoluted linked groupings that exist between the specified species.
Keywords: Characters; Cyathodium; Distribution; India; Species diversity